Coming of age with quantum information : notes on a Paulian Idea : selected vorrespondence, 1995-2001 - Fuchs, Christopher A., 1964-; Cambridge eBooks (Cambridge : Cambridge University Press, 2011)
A passionate and personal account of the early days of quantum information and quantum computing, this unique book is a collection of more than 500 letters between the author and many of the founders of these intriguing fields. Christopher A. Fuchs is one of the most penetrating modern thinkers on the philosophical foundations of quantum mechanics. This remarkable book follows his journey as he comes to grips with the quantum world. It contains correspondence with Charles Bennett, Gilles Brassard, Rolf Landauer, N. David Mermin, Michael Nielsen, Asher Peres, John Preskill, Abner Shimony, William Wootters, Anton Zeilinger, and many others. Filled with diary entries, anecdotes, historical selections, and research ideas, this book will fascinate physicists, philosophers, and historians of science.
Machine generated contents note: 1. Letters to David Baker; 2. Letters to Howard Baker; 3. Letters to Howard Barnum; 4. Letters to Paul Benioff; 5. Letters to Charlie Bennett; 6. Letters to Herb Bernstein; 7. Letters to Doug Bilodeau; 8. Letters to Gilles Brassard; 9. Letters to Jeffrey Bub; 10. Letters to Carlton Caves; 11. Letters to Greg Comer; 12. Letters to Charles Enz; 13. Letters to Henry Folse; 14. Letters to Bob Griffiths; 15. Letters to Adrian Kent; 16. Letters to Rolf Landauer; 17. Letters to Hideo Mabuchi; 18. Letters to David Mermin; 19. Letters to David Meyer; 20. Letters to Jeff Nicholson; 21. Letters to Michael Nielsen; 22. Letters to Asher Peres; 23. Diary of a carefully worded paper: more letters to Asher Peres; 24. Letters to John Preskill; 25. Letters to Joseph Renes; 26. Letters to Mary Beth Ruskai; 27. Letters to Rüdiger Schack; 28. Letters to Robert Schumann; 29. Letters to Abner Shimony; 30. Letters to Jon Waskan; 31. Letters to Bill Wootters; 32. Letters to Anton Zeilinger; 33. Other letters; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Fuchs, Christopher A., -- 1964- -- Correspondence; Physicists -- Sweden -- Correspondence; Quantum theory; Electronic books